Earlier versus Later Start of Antiretroviral Therapy in HIV-Infected Adults with Tuberculosis - Blanc, François-Xavier; Sok, Thim; Laureillard, Didier; Borand, Laurence; Rekacewicz, Claire; Nerrienet, Eric; Madec, Yoann; Marcy, Olivier; Chan, Sarin; Prak, Narom; Kim, Chindamony; Lak, Khemarin Kim; et al. (The New England journal of medicine, 2011)
When to initiate antiretroviral therapy in patients with newly diagnosed HIV infection and TB has been debated. In this study from Cambodia, giving antiretrovirals 2 weeks after the start of TB therapy was superior to therapy begun at 8 weeks, with a decrease in mortality. Tuberculosis is a major cause of death in persons infected with the human immunodeficiency virus (HIV), especially in resource-limited settings. 1 , 2 Despite effective tuberculosis therapy, mortality is particularly high among patients with severe immunosuppression. 3 , 4 Although mortality among HIV-infected patients has been reported to be approximately 30% within the first 2 months of tuberculosis treatment if antiretroviral therapy (ART) is withheld, 5 the timing for starting ART in patients with tuberculosis has remained unclear. Arguments that support delayed initiation of ART include concern about the combined toxic effects of drugs, an increased risk of the immune reconstitution inflammatory syndrome (IRIS), and . . .